2022
DOI: 10.1371/journal.pone.0264430
|View full text |Cite
|
Sign up to set email alerts
|

Laminin N-terminus α31 is upregulated in invasive ductal breast cancer and changes the mode of tumour invasion

Abstract: Laminin N-terminus α31 (LaNt α31) is an alternative splice isoform derived from the laminin α3 gene. The LaNt α31 protein is enriched around the terminal duct lobular units in normal breast tissue. In the skin and cornea the protein influences epithelial cell migration and tissue remodelling. However, LaNt α31 has never been investigated in a tumour environment. Here we analysed LaNt α31 in invasive ductal carcinoma and determined its contribution to breast carcinoma invasion. LaNt α31 expression and distribut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In tumorigenesis, once activated, these proteins promote cell proliferation, migration, differentiation, and metastasis ( 98 , 99 ). Indeed, laminin facilitates cell migration and invasion in invasive ductal breast cancer ( 103 ), gastric cancer ( 104 ), and bladder cancer ( 105 ). In addition, laminin may be correlated with the immune response in ovarian cancer ( 104 ).…”
Section: Ecm In Pa-cxpa Progressionmentioning
confidence: 99%
“…In tumorigenesis, once activated, these proteins promote cell proliferation, migration, differentiation, and metastasis ( 98 , 99 ). Indeed, laminin facilitates cell migration and invasion in invasive ductal breast cancer ( 103 ), gastric cancer ( 104 ), and bladder cancer ( 105 ). In addition, laminin may be correlated with the immune response in ovarian cancer ( 104 ).…”
Section: Ecm In Pa-cxpa Progressionmentioning
confidence: 99%
“…37 Increased expression is associated with breast ductal carcinoma and in vitro overexpression leads to a change in the mode of breast cancer cell invasion through LM-rich matrices. 38 LaNt α31 is also transiently upregulated during re-epithelialization of ex vivo corneal burn wounds and in limbal stem cell activation assays. 36 In epidermal and corneal keratinocytes, knockdown or overexpression experiments revealed that modulating LaNt α31 levels leads to reduced migration rates and changes to cell-to-matrix adhesion.…”
Section: Introductionmentioning
confidence: 96%
“…LaNt α31 is expressed in the basal layer of epithelia in the skin, 24 cornea 36 and digestive tract, the ECM around terminal duct lobular units of the breast and alveolar air sacs in the lung, and is widely expressed by endothelial cells 37 . Increased expression is associated with breast ductal carcinoma and in vitro overexpression leads to a change in the mode of breast cancer cell invasion through LM‐rich matrices 38 . LaNt α31 is also transiently upregulated during re‐epithelialization of ex vivo corneal burn wounds and in limbal stem cell activation assays 36 .…”
Section: Introductionmentioning
confidence: 99%